Fluid Mechanics of Plankton - Yamazaki, Hidekatsu; Strickler, J. Rudi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The cooperation between plankton biologists and fluid dynamists has enhanced our knowledge of life within the plankton communities in ponds, lakes, and seas. This book assembled contributions on plankton-flow interactions, with an emphasis on syntheses and/or predictions. However, a wide range of novel insights, reasonable scenarios, and founded critiques are also considered in this book.